PENGEMBANGAN GAME EDUKASI PADA MATA PELAJARAN KOMPUTER GRAFIS KELAS XI DKV DI SMK NEGERI 4 SUNGAI PENUH - Aidil Fitra Hadi; Haris Kurniawan; Herisvan Hendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of students in the Computer Graphics class XI DKV at SMK Negeri 4 Sungai Penuh. The lack of variety in learning media and low student motivation in understanding computer graphics theory were the main problems identified. The purpose of this study was to develop educational game learning media for the Computer Graphics class XI DKV at SMK Negeri 4 Sungai Penuh and to determine the level of validity and practicality of this educational game learning media for the Computer Graphics class XI DKV at SMK Negeri 4 Sungai Penuh. The method used was Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The product developed was the educational game "Ninja Adventure," which integrates game missions with a quiz on introductory computer graphics. The research instruments included validation by media experts, validation by material experts, and practicality tests by teachers and students to assess the product's validity and practicality as a learning medium. The results of the study indicate that the developed educational game meets the criteria for validity and practicality. Validity testing by media experts yielded an average score of 81.94% (highly valid), while material validation achieved 78.39% (highly valid). Practicality testing by teachers yielded an average score of 84.72% (highly practical), while student practicality was 77.98% (highly practical). Based on these results, this educational game is deemed suitable for use as an alternative learning medium capable of increasing student learning motivation and providing a more interactive and enjoyable learning experience.